Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 1 - Section 1.6 - Properties of Integral Exponents - Exercise Set: 68

Answer

$=-\frac{x^{12}}{8}$

Work Step by Step

RECALL: (i) The products-to-powers rule states that: $(ab)^n=a^nb^n$ (ii) The power rule states that: $(a^m)^n=a^{mn}$ (iii) The negative-exponent rule states that: $a^{-m} = \dfrac{1}{a^m}$ and $\dfrac{1}{a^{-m}} = a^m$ Use the products-to-powers rule to find: $=(-2)^{-3}(x^{-4})^{-3}$ Use the power rule to find: $=(-2)^{-3}x^{-4(-3)} \\=(-2)^{-3}x^{12}$ Use the negative-exponent rule to find: $=\frac{1}{(-2)^3}\cdot x^{12} \\=\frac{1}{-8} \cdot x^{12} \\=-\frac{x^{12}}{8}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.